WHEELCHAIR DEVELOPMENT DESIGN WITH BRAKE SUPPORT FOR INDEPENDENT MOBILITY PERSONS WITH MODERATE PHYSICAL DISABILITIES - Fuad, Saftrian Mukhlizul; Ciptandi, Fajar; Hadiansyah, Mahendra Nur (Ide dan Dialog Desain Indonesia (Idealog), 2023)
The population of Indonesia in 2022 will reach 27,536 million people, of which 17.5 millionpeople are people with disabilities. In this context, disability refers to physical or mental limitations limiting a person's social interaction. The primary function of a wheelchair brake is to control the speedand movement of the wheelchair and its equipment. However, the manual wheelchair braking systemis still not ef ective enough to overcome steep roads. Accessibility for people with disabilities is greatlyinfluenced by environmental and structural factors, especially in areas where the streets are long or steep. To increase accessibility for people who use manual wheelchairs and have physical limitations, particular research was carried out. The method used in this research uses a design thinking frameworkthat begins with a data collection process through interviews, observations, documents, and validationusing triangulation of data sources to conclude, then carrying out the design process using experimental methods and validating wheelchair users with disabilities. This research aims to address the mobilitychallenges of people with physical disabilities who use manual wheelchairs in areas with steeptopography. The result of this research is that an innovative concept of using brake accessories onmanual wheelchairs has been developed. Keywords : disability, wheelchair, accessibility, physical limitations